2021
DOI: 10.1038/s41467-021-25018-3
|View full text |Cite|
|
Sign up to set email alerts
|

Spectroscopic evidence for a large spot on the dimming Betelgeuse

Abstract: During October 2019 and March 2020, the luminous red supergiant Betelgeuse demonstrated an unusually deep minimum of its brightness. It became fainter by more than one magnitude and this is the most significant dimming observed in the recent decades. While the reason for the dimming is debated, pre-phase of supernova explosion, obscuring dust, or changes in the photosphere of the star were suggested scenarios. Here, we present spectroscopic studies of Betelgeuse using high-resolution and high signal-to-noise r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our modelling, however, shows that the localised presence of the newly formed dust in the line of sight of the star would go undetected at these wavelengths using these observational methods. Alexeeva et al (2021) conclude from TiO line fitting to spectroscopic observations in the NIR at wavelengths shorter than 1 µm that only a cool photospheric patch could reproduce their observations. Montargès et al (2021), however, found that a cool spot model produces a reduction of the flux at 1.6 µm that is significantly larger than what is observed during the dimming event.…”
Section: Detecting Dust That Potentially Formed During the Great Dimmingmentioning
confidence: 68%
See 1 more Smart Citation
“…Our modelling, however, shows that the localised presence of the newly formed dust in the line of sight of the star would go undetected at these wavelengths using these observational methods. Alexeeva et al (2021) conclude from TiO line fitting to spectroscopic observations in the NIR at wavelengths shorter than 1 µm that only a cool photospheric patch could reproduce their observations. Montargès et al (2021), however, found that a cool spot model produces a reduction of the flux at 1.6 µm that is significantly larger than what is observed during the dimming event.…”
Section: Detecting Dust That Potentially Formed During the Great Dimmingmentioning
confidence: 68%
“…Multiple hypotheses regarding the physical processes responsible for this great drop in brightness have been proposed. These include dust nucleation above the surface obscuring the star (Safonov et al 2020;Cotton et al 2020;Levesque & Massey 2020), an ejection of dense chromospheric material from the southern hemisphere subsequently forming molecules and dust (Dupree et al 2020), photospheric cooling as a result of stochastic convective motions and pulsations (Dharmawardena et al 2020;Harper et al 2020;Alexeeva et al 2021), and a 'molecular plume' causing a local opacity increase (Kravchenko et al 2021;Davies & Plez 2021). Notes.…”
Section: Introductionmentioning
confidence: 99%